Implementation Of Multicultural Education In Facing The Challenges Of Globalization - Haris Firmansyah (Sean Institute, 2024)
Multicultural education plays an important role in preserving Indonesian culture in the era of globalization. Globalization brings challenges in intercultural interaction and human mobility, making the implementation of multicultural education in schools crucial. This research aims to identify the concepts and principles of multicultural education, as well as to explore strategies in facing the challenges of globalization on multicultural education. The research method used is a literature review to identify the concepts and principles of multicultural education. The data was analyzed to explore strategies in overcoming the challenges of globalization on multicultural education. The results showed that multicultural education is important in strengthening tolerance, appreciation of diversity, and intercultural collaboration. Globalization challenges such as cultural stereotypes, language differences and inequality of access can be addressed through inclusive curriculum development, training for educators and collaboration between educational institutions. By implementing these strategies, educational institutions can face the challenges of globalization more effectively and create inclusive and meaningful learning environments for all students.